THE SMALL TOURISM ENTERPRISES SUSTAIN AND PLAN THEIR BUSINESSES DURING COVID-19 IN BANGKOK - Bai, Yadan (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
As the epidemic spreads around the world, it seriously affects the global economy and tourism. The COVID-19 outbreak is sudden and there is no knowing when it will end. Keeping an angular distance is an effective way to avoid the spread of the virus, which has also led to the shutdown of the tourism industry and confusion among travel workers about the future. This article will explore how small tourism enterprises can respond and plan to maintain their survival in the context of COVID-19. In qualitative research, non-probability purposive sampling technique, depth interview and open questions were used to collect data. In this paper, constant comparison analysis method was used. Small enterprises had virtually no business during the epidemic, and not all of them were able to get government help because of the large number of small businesses. Small enterprises should have the initiative to find their own way to survive. Small enterprises are highly flexible and can adjust their strategies quickly to the situation.